ANO3 Mutations in Chinese Dystonia: A Genetic Screening Study Using Next-Generation Sequencing - Li, Shanglin; Wang, Lin; Yang, Yingmai; Ma, Jun; Wan, Xinhua (Frontiers in Neurology, 2020)
Background：Dystonia-24 (DYT24) is a monogenic autosomal dominant dystonia caused by mutations in the gene ANO3, which has shown phenotypic and genotypic heterogeneity according to previous reports. Objective: To screen and identify ANO3 mutations in a cohort of patients with dystonia in China and to expand the spectrum of DYT24. Methods: This study screened ANO3 mutations in 187 Chinese dystonia patients using next-generation sequencing (NGS). In silico investigations were conducted in detected ANO3 variants and co-segregation analysis was carried out if applicable. The effects of identified variants were classified according to the standards and guidelines of the American College of Medical Genetics and Genomics (ACMG). Results: Four different variants were identified in four unrelated dystonia patients, including three missense variants [c.1789G>C (p.V600L), c.182A>C (p.E61A), c.787A>G (p.M263V)] and one splice site change (c.1714-3T>C). The novel missense mutation c.1798G>C (p.V600L), identified in a teenaged girl with generalized dystonia, showed high pathogenicity and was classified as “likely pathogenic” according to ACMG guidelines. Of note, she responded well to deep brain stimulation. Conclusion: Our study helps expand the mutational and clinical spectrum of DYT24 due to ANO3 mutations by further reporting four variants. Rare ANO3 variants appear to represent an uncommon cause of dystonia in China.